Sleep Laboratory Test Referrals in Canada: Sleep Apnea Rapid Response Survey - Jessica Evans; Robert Skomro; Helen Driver; Brian Graham; Irvin Mayers; Louise McRae; Joseph Reisman; Corneliu Rusu; Teresa To; John Fleetham (Canadian Respiratory Journal)
BACKGROUND: An estimated 5.4 million Canadian adults have been diagnosed with sleep apnea or are at high risk of experiencing obstructive sleep apnea (OSA). There are no recent Canadian data regarding access to and predictors of referral for diagnostic testing in these populations.